Associations between gut microbiota and Parkinson disease: A bidirectional Mendelian randomization analysis - Jiang, Li; Li, Jin‐chen; Tang, Bei‐sha; Guo, Ji‐feng (European journal of neurology, 2023)
Parkinson disease (PD)-associated alterations in the gut microbiome have been observed in clinical and animal studies. However, it remains unclear whether this association reflects a causal effect in humans. We performed two-sample bidirectional Mendelian randomization using summary statistics from the international consortium MiBioGen (N = 18,340), the Framingham Heart Study (N = 2076), and the International Parkinson's Disease Genomics Consortium for PD (33,674 cases and 449,056 controls) and PD age at onset (17,996 cases). Twelve microbiota features presented suggestive associations with PD risk or age at onset. Genetically increased Bifidobacterium levels correlated with decreased PD risk (odds ratio = 0.77, 95% confidence interval [CI] = 0.60-0.99, p = 0.040). Conversely, high levels of five short-chain fatty acid (SCFA)-producing bacteria (LachnospiraceaeUCG010, RuminococcaceaeUCG002, Clostridium sensustricto1, Eubacterium hallii group, and Bacillales) correlated with increased PD risk, and three SCFA-producing bacteria (Roseburia, RuminococcaceaeUCG002, and Erysipelatoclostridium) correlated with an earlier age at PD onset. Gut production of serotonin was associated with an earlier age at PD onset (beta = -0.64, 95% CI = -1.15 to -0.13, p = 0.013). In the reverse direction, genetic predisposition to PD was related to altered gut microbiota composition. These results support a bidirectional relationship between gut microbiome dysbiosis and PD, and highlight the role of elevated endogenous SCFAs and serotonin in PD pathogenesis. Future clinical studies and experimental evidence are needed to explain the observed associations and to suggest new therapeutic approaches, such as dietary probiotic supplementation.